Improving the thermal performance of PVC windows with pultruded thermoplastic reinforcement - Kirill Minchenkov; Sergey Gusev; Ivan Sergeichev; Alexander Safonov (Scientific Reports)
Abstract Today, composite profiles of constant cross section are widely used in advanced engineering structures. The use of composite profiles in window and door structures can reduce thermal bridging and reduce energy consumption for heating and cooling. This article focuses on the production of new, thermoplastic-based structural pultruded profiles and their application in a PVC (polyvinylchloride) window structure as a reinforcement. The heat transfer model was developed to determine die temperature and pulling speed for pultrusion of the 30 × 20 × 3.5 mm tube and a 31.5 × 25.0 × 3.5 mm channel from tapes. The microscopy results demonstrated full consolidation of all tapes in the material, thus confirming proper selection of pultrusion parameters. The mechanical tests results of the welded angle joint show that the window structure with composite reinforcement can be twice as strong as the steel reinforced one. This was achieved by welding the composite reinforcement simultaneously with welding of the PVC frame on a butt welding machine. The results of the hot box test show that the U-value of the window sash and frame with the composite reinforcement is 12% lower than that of a window with a steel reinforcement. The U-value of the window with composite reinforcement is 1.47 W/(m2·K), and that of the steel reinforced window is 1.55 W/(m2·K). Thus, the windows with composite reinforcement have low thermal transmittance complying with building regulations in various countries, and their use is permitted in northern climatic zones.